(untitled) (Práxis Educativa, 2023)
The purpose of this text is to present some theoretical and methodological considerations for the study of social representations, in the educational field, which have been integrated on a proposal for the analysis of their discursive dimension. based on the natural logic. I describe the central components of this proposal and show that the singularity of this approach is that it highlights the role that language plays in the construction of social representations, the understanding of the relationship between subject and the object of presentations and his/her commitment in what he/she says. Based on my research in the field of education, I exemplify the proposal with a study on the 2013 Mexican Educational Reform. Keywords: Discourse. Social representations. Education.